Implicações socioculturais do processo de ensino de português para falantes de outras línguas no contexto virtual do Teletandem - Ramos, Karin Adriane Henschel Pobbe [UNESP] (My University, 2013)
This study aims to discuss, by assuming the perspective of the Discourse Analysis, the social and cultural implications of the process of teaching Portuguese to foreigners in the virtual context of Teletandem. It also intends to evaluate the levels of Critical Language Awareness presented by the participants, in relation to the linguistic, discursive and social dimensions of the analysis. The data were collected in 2011 in interactions between students from Unesp/Assis and students from North-American universities. The research has been guided by the following questions: (a) how social and historical changes are reflected in language uses; (b) how these implications appear in the context of Teletandem; (c) how is it possible to evaluate the levels of Critical Language Awareness between the participants related to the social dimension of the discourse.

Este estudo tem como objetivo discutir, sob a perspectiva dos pressupostos teóricos da Análise Crítica do Discurso, as implicações socioculturais do processo de ensino de português para falantes de outras línguas no contexto virtual do Teletandem. Também busca avaliar os níveis de Conscientização Crítica da Linguagem evidenciados pelos participantes, no que tange às dimensões linguísticas, discursivas e sociais da análise. Os dados foram coletados durante o ano de 2011 em interações de alunos da Unesp de Assis com alunos de universidades norte- -americanas. A pesquisa tem sido norteada pelas seguintes perguntas: (a) de que modo mudanças históricas e sociais estão refletidas nos usos da linguagem; b) como se dão essas implicações no contexto do Teletandem; c) de que forma é possível evidenciar os níveis de Conscientização Crítica da Linguagem entre os participantes no que diz respeito à dimensão social do discurso.
Social and cultural implications of the process of teaching Portuguese to foreigners in the virtual context of Teletandem
Keywords: Portuguese for foreigners; Teletandem; Critical language awareness; Português para falantes de outras línguas; Teletandem; Conscientização crítica da linguagem